Al-Taḥlīl al-Taqābulī Bayna al-Tahakkum fī al-Lugah al-Arabīyah wa Antifrasis fī al-Lugah al-Indūnīsīyah - Hafidz, Muhammad (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2023)
Contrastive analysis helps teach foreign languages ​​because of several assumptions: the more significant the difference between the first and second languages, the more acute the learning difficulties. The results of the comparison between the first and second languages are needed to predict the difficulties of learning a foreign language. This research compares antiphrasis Arabic and Indonesian using comparative steps of Contrastive Analysis. The results of this research are: 1) Similarities between the antiphrasis of Arabic and Indonesian are both expressions that have the opposite meaning; 2) Difference between antiphrasis Arabic and Indonesian: a). In Arabic antiphrasis, the expressions used are not only mocking by praising, but giving warnings with expressions of giving good news and threatening expressions with expressions of giving promises; b). In Indonesian antiphrasis, most expressions are mocking in a praising style.